Mobilitätsverhalten potentieller Radfahrer in Dresden. Eine empirische Analyse. - Manteufel, Rico (My University, 2015)
Mit der Arbeit soll untersucht werden, durch welche Merkmale sich die Dresdner Radfahrer beschreiben lassen und inwieweit noch Potenziale zur Steigerung des Radverkehrsanteils, hinsichtlich bestimmter Personengruppen oder Wegeklassen, bestehen. Dies soll in Form einer Datenauswertung der SrV-Untersuchung (System repräsentativer Verkehrserhebungen) von 2013 geschehen, wobei nur "potenzielle Radfahrer" betrachtet werden sollen. Dabei soll, jeweils auf Personen- und Wegeebene, sowohl eine deskriptive Analyse erfolgen, als auch die Diskriminanzanalyse als statistisches Verfahren zur Anwendung kommen.

Before the German reunification, Dresden was a city of motorized traffic and cyclist were rare. But in the 90's began a change of transport policy and cycling became more important. This Master Thesis wants to show the current standing of cycling in Dresden. Thats why the results of the "SrV"-study should be analysed with regard to potential cyclists and their journeys. As methods were used a descriptive analysis and the linear discriminant analysis, both used at a personal and journey-specific level of data. As a result, Dresden have to do much more to become a good "cycling-city", so the bike-level wasn't really high in the year 2013. Instead the car is still the mostly used transport vehicle and the proportion in the Modal-Split is only slowly sinking. But this study shows typical characteritics of cyclists and cycling journays of Dresden, so there is a basis to get more people involved to cycle and become a more eco-friendly city.
Mobility behaviour of potential cyclists in Dresden. An empirical analysis.
Keywords: Verkehr; Individualverkehr; Fahrrad; Fahrradverkehr; Mobilität; Verkehrsverhalten; Verkehrsmittelwahl; Verkehrsentwicklung; Potenzialanalyse; Diskriminanzanalyse; Mobilitätsverhalten; Mobilitätsforschung; Radverkehrsförderung; Verkehrsdaten; Datenauswertung